Antioxidant potency of ethanolic extract of Kemuning leaves (Murraya paniculata (L) Jack ) in vitro - Rohman, Abdul; Riyanto, Sugeng (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
Antioxidants are the compounds capable to inhibit free radical reactions in the human body. This research was aimed to identify the antioxidant potency of ethanolic extract of kemuning leaves in vitro by using linoleic-thiocyanate and DPPH (2,2-diphenyl-1-picryl hydrazyl) methods. The ethanolic extract of kemuning leaves was diluted in various concentrations i.e. 1%,5% and 10% and determined their antioxidant potencies. By using linoleic-thiocyanate method, the result suggested, that ethanolic extract of 1%; 5 % and 10 % showed antioxidant potencies and had significant different absorbances (P < 0,05). The antioxidant potencies of ethanolic extract with different concentrations were also measured by DPPH method and the result showed that ethanolic extracts of kemuning leaves revealed the antioxidant activity with the IC50 of 126,17 µg/ml, 15 times lower than that of vitamin E (IC of 8,27 µg/ml). The antioxidant activity of kemuning leaves probably due to the flavonoid content.